Smart ambulance using IoT for blood transfer facilities - Mohamed A. Torad; Yahia H. Hossamel-din (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
In case of an accident occurrence, ambulance try to transport wounded and injured people to the nearest hospital, but if the injured persons need an urgent blood transfer, the emergency reception (ER) can check the availability of the needed blood type and quantity. If it is available, the emergency reception accepts the injured person, but if it is not available, the reception reroutes the ambulance to the nearest hospital which have the required blood type and quantity. So, a system created that save that wasted time to save injured people life as possible.  So, we create a system that save that wasted time to save injured people life as possible. So, the main contribution in this paper is selecting and determining the nearest hospital that own the proper blood types to save injurjed people lives using dijkstra algorithm. In this study, we use an android application at the ambulance which permit the paramedic to login and select the required blood type and quantity needed after determining the injured person’s blood type and the android application automatically determine the nearest hospital using the best shortest path algorithm (SPA) after checking the database and generate a pin code for the paramedic to deliver it with injured person to the ER and get the needed blood. This process will consequently decrease the used blood quantity from the database.